Revitalizing West Javanese Culture: Enhancing Batik Kasumedangan's Marketability on National and International Fronts - Mariana Rachmawati; Deden Sutisna; R.Adjeng Mariana F; Suharno Pawirosumarto; Lilis Yuaningsih; Cucu Hodijah; Santi Maria; Wandi Kurniadi (Community Engagement and Emergence Journal (CEEJ), 2024)
The Ministry of Industry continues to explore the potential of the batik industry, particularly in West Java, with the aim of enhancing competitiveness and the welfare of batik and weaving artisans. In West Java alone, there are 27 districts and cities actively producing batik with a variety of motifs, employing around 4,000 batik artisans. According to the Minister of Industry, Saleh Husin, West Java boasts a rich array of textile creations, including batik and weaving, influenced by its agrarian and industrial culture which fosters openness and dynamism among its people. This increasing innovation and preservation of West Javanese batik will contribute to its greater recognition. The batik from West Java is highly diverse, featuring bright and basic colors, with each motif and color carrying its own significance. Despite these attributes, in 2021, the performance of the Traditional Kasumedangan Batik SMEs in West Java was relatively low, failing to rank among the top ten textile exporters in Indonesia. The underperformance of these SMEs can be attributed to ineffective strategic management, which has been hindered by external environmental factors, inadequate company resources, and ineffective competitive strategies, ultimately resulting in very low business performance.